1310. Antimicrobial Activity of Ceftazidime-Avibactam and Other New β-Lactamase Inhibitor Combinations Tested against Bacterial Isolates from Pediatric Patients from US Medical Centers (2020-2021). (15th December 2022) - Sader, Helio S; Carvalhaes, Cecilia G; Shortridge, Dee; Duncan, Leonard R; Castanheira, Mariana
Abstract: Background: The US FDA expanded the approval of ceftazidime-avibactam (CAZ-AVI) to include pediatric patients aged ≥ 3 months in 2019. We evaluated the in vitro activities of CAZ-AVI, ceftolozane-tazobactam (C-T), meropenem-vaborbactam (MEM-VAB), imipenem-relebactam (IMI-REL), and comparators against Enterobacterales (ENT; n =2, 391) and P. aeruginosa (PSA; n =414) isolates causing infection in pediatric patients from US medical centers. Methods: Among 21, 332 organisms (1/patient) collected in 2020-2021 via the INFORM Surveillance Program, 2, 805 (13.1%) were from pediatric patients (≤ 17 years-old [yo]). The isolates were consecutively collected from 69 US medical centers and susceptibility tested by reference broth microdilution methods. Susceptibility results were stratified by patient age (≤ 1 yo [1, 040 isolates], 2-5 yo [580], 6-12 yo [651], and 13-17 yo [534], and by infection type. ENT isolates with an ESBL phenotype were screened for β-lactamase genes by whole genome sequencing. Results: CAZ-AVI and MEM-VAB showed complete activity (100.0% susceptible [S]) against Enterobacterales, whereas C-T and IMI-REL showed limited activity against some organisms (Table). MEM, ceftriaxone (CRO), and gentamicin (GEN) were active against 99.8%, 87.5%, and 93.0% of Enterobacterales, respectively. Enterobacterales susceptibility to CRO varied from 84.7% (6-12 yo) to 89.8% (13-17 yo), susceptibility to GEN varied from 91.9% (6-12 yo) to 94.0% (≤ 1 yo), and susceptibility to the multidrug-resistant (MDR) phenotype varied from 3.7% (≤1 yo) to 4.8% (13-17 yo). CAZ-AVI (99.5%S), C-T (99.8%S), and IMI-REL (98.4%S) were the most active agents against the PSA collection, but CAZ-AVI and C-T showed greater activity than IMI-REL against PSA-resistant subsets. MEM-VAB and MEM exhibited similar activity against PSA (91.3% inhibited at ≤ 2 mg/L for both agents). PSA overall susceptibility for MEM was 91.3%, varying from 87.3% (13-17 yo) to 93.2% (2-5 yo).Piperacillin-tazobactam (PIP-TAZ) was 87.4%, varying from 85.1% (6-12 yo) to 90.1% (13-17 yo). Conclusion: CAZ-AVI and MEM-VAB were the most active agents against Enterobacterales and CAZ-AVI. C-T was the most active agents against PSA. Susceptibility differences were observed among age groups. Disclosures: Helio S. Sader, MD, PhD, AbbVie: Grant/Research Support|Cidara: Grant/Research Support|Melinta: Grant/Research Support|Nabriva Therapeutics: Grant/Research Support|Pfizer: Grant/Research Support Cecilia G. Carvalhaes, MD, PhD, AbbVie: Grant/Research Support|Cidara: Grant/Research Support|Melinta: Grant/Research Support|Pfizer: Grant/Research Support Dee Shortridge, PhD, AbbVie: Grant/Research Support|JMI Laboratory: Employee|Melinta: Grant/Research Support|Menarini: Grant/Research Support|Shionogi: Grant/Research Support Leonard R. Duncan, PhD, AbbVie: Grant/Research Support Mariana Castanheira, PhD, AbbVie: Grant/Research Support|Cidara: Grant/Research Support|GSK: Grant/Research Support|Melinta: Grant/Research Support|Pfizer: Grant/Research Support|Shionogi: Grant/Research Support.